Possibilities of Import Substitution in the Russian Pharmaceutical Market - Peskova, Olga S. (Asian Journal of Pharmaceutics (AJP), 2017)
The article investigates the possibilities of import substitution in the Russian pharmaceutical market, the problems of the reaction of the Russian pharmaceutical industry to foreign sanctions foreign pharmaceutical firms. Recently, the Russian government’s policy is aimed at the development of its own economy, domestic production that entails new challenges and at the same time, the prospects of development of the domestic pharmaceutical industry.